Type depositories of Chalcidoidea (Hymenoptera) species described from the Department of Zoology, Aligarh Muslim University, India - Hayat, Mohammad; Khan, F. R.; Badruddin, S. M. A. (Zootaxa, 2011)
The type specimens of 717 chalcidoid species described by taxonomists from the Department of Zoology, Aligarh Muslim University, India, and their depositories are tabulated. Table 1 lists the holotypes and other type specimens of the species deposited in the Natural History Museum, London, England (BMNH), National Zoological Collections, Zoological Survey of India, Kolkata, India (NZSI), Forest Entomology Division, Forest Research Institute, Dehra Dun, India (FRI), National Pusa Collections, Division of Entomology, Indian Agricultural Research Institute, New Delhi, India (NPC), and the Insect Collection, Department of Zoology, Aligarh Muslim University, Aligarh, India (ZDAMU). The holotypes and lectotypes of 700 species are distributed as follows: BMNH (175), NZSI (34), FRI (28), NPC (131), and ZDAMU (332). The holotypes of 17 species could not be located in ZDAMU, but all of these species are represented by paratypes. A further 23 species whose types are not located in ZDAMU are listed in Table 2.